2015
DOI: 10.2527/jas.2014-7356
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of activated diatomaceous clay in reducing the toxicity of zearalenone in rats and piglets1

Abstract: Two experiments were conducted to evaluate the efficacy of an activated diatomaceous clay (ADC) in reducing the toxic effects of zearalenone (ZEA) in the diet of rats and piglets. In the rat experiment, 90 Sprague-Dawley female weanling rats with an initial BW of 45 ± 1.0 g were assigned to 1 of 6 dietary treatments for 28 d in a completely randomized design (CRD) with a 2 × 3 factorial arrangement (0 or 6 mg ZEA/kg feed and 0, 1, and 5 g ADC/kg feed). In the piglet experiment, 64 female piglets ([Large White … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…By comparison, acidic and neutral conditions promote interaction between ZEN and yeast cell walls with more stable complexes than in alkaline conditions [38]. Consequently, modified clays with organic cations have been developed to improve ZEN adsorption, which provide sufficient space between the layers to react with mycotoxin with a relatively less polarity with the appropriate electrical charging [6,3941]. These modified surface properties lead to greater hydrophobicity by exchanging the structural load balance cations with high molecular weight quaternary amines [10].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, acidic and neutral conditions promote interaction between ZEN and yeast cell walls with more stable complexes than in alkaline conditions [38]. Consequently, modified clays with organic cations have been developed to improve ZEN adsorption, which provide sufficient space between the layers to react with mycotoxin with a relatively less polarity with the appropriate electrical charging [6,3941]. These modified surface properties lead to greater hydrophobicity by exchanging the structural load balance cations with high molecular weight quaternary amines [10].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the cytotoxic effects of ZEN in the liver [ 60 ], ingestion of this endocrine disruptor (ED) should be considered as a threat to hepatic functions in humans as well. Although little or no report can be found from human studies, ZEN alters the level and activity of some liver enzymes (such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT), and lactate dehydrogenase (LDH)) in the examined species, including rabbits [ 58 ], rats [ 59 , 61 ], and pigs [ 44 ]. In addition to the adverse effects of ZEN on liver functions, the metabolization of ZEN continues in the kidneys where it exerts further destructive effects.…”
Section: Discussionmentioning
confidence: 99%
“…ZEN, as most of the EDs, effects the reproductive system as well. These ED effects are broadly documented among the affected organ systems, and in this respect not only females but males are targets of ZEN (and other EDs) as well [ 61 , 64 , 65 ]. ZEN can penetrate through the blood brain barrier (like other EDs [ 66 ]), and modify hypothalamic and pituitary functions in all examined species.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported that clay enterosorbent at the levels of 5 or 10 g/kg was able to reduce the estrogenic effect of ZEA on vulvar swelling in postweaning female pigs [25]. Moreover, Denli et al demonstrated that activated diatomaceous clay could effectively spare the estrogenic effect of ZEA on uterus and ovaries in rats and pigs [26]. The addition of a modified calcium montmorillonite alleviated some of the reproductive effects of ZEA on the relative weight of genital organs in postweaning piglets [24,27].…”
Section: Discussionmentioning
confidence: 99%